Dietary Capsaicin Reduces Chemically Induced Rat Urinary Bladder Carcinogenesis - Altieri, Marcelo Augusto [UNESP] (2023)
Capsaicin (CAP) is the compound responsible for pungency in chili peppers, presenting several biological properties. But its general safety and effectiveness in the context of carcinogenesis has not been fully clarified. Thus, the present study evaluated whether dietary CAP modifies the development of urothelial lesions induced by the carcinogen N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN) in male Sprague–Dawley rats. Animals were randomly allocated into 6 groups: G1 – treated with 0.05% BBN in drinking water (weeks 1–12) and received a balanced diet (weeks 1–20); G2 and G3—treated with BBN (weeks 1–12) and received a balanced diet with 0.01 or 0.02% CAP (weeks 1–20), respectively; G4 and G5- only received a balanced diet with 0.01 or 0.02% CAP (weeks 1–20), respectively; G6 – only received a balanced diet (weeks 1–20). At the end of week 20, the incidence and types of urothelial lesions, proliferating cell nuclear antigen (PCNA) labeling index, and matrix metalloproteinases (MMP) 2 and 9 activities were analyzed. A significant reduction was observed in the incidence and multiplicity of simple (p = 0.020 and p = 0.011) and nodular/papillary (p = 0.030 and p = 0.003) hyperplasias and papillomas/carcinomas (p = 0.023 and p = 0.020), epithelial proliferation (p = 0.007) and in the activity of the intermediate form of MMP-2 (p < 0.001) and pro-MMP-9 activities (p < 0.002), in BBN + 0.02% CAP (G3) group in comparison to BBN (G1) group. Capsaicin intake per se did not alter body weight, liver and kidney weights, urothelial histology or serum biochemical parameters. Thus, dietary CAP was safe and showed a protective effect against rat BBN-induced urothelial carcinogenesis.